Innovative technologies in construction - Novikov, D.; Lavrukhina, K.; Kushik-Strelnikov, Ya. (Ways to Improve Construction Efficiency, 2020)
The article considers theoretical and practical bases of tendencies of development of construction market of Ukraine; determined that the directions of innovative business in construction are the following: a) the purchase of advanced foreign technologies and the organization of production of new products; b) purchase of progressive materials, machines and equipment for construction organizations; c) purchase of domestic and foreign patents for further organization of own production of building materials; d) services of foreign construction companies in the production of construction works using new technologies; e) conducting own R&D; f) implementation of own innovative architectural and design developments; g) training of workers and specialists in new technologies, skills in working with new mechanisms and building materials. Conclusions have been made about the need to introduce innovative technologies in construction; directions for stimulating the development of the construction market based on the introduction of innovative technologies are proposed. It is determined that in recent years there have been global changes in the main economic and production indicators of the external environment that affect the activity of construction enterprises. The most important of them are: complication of production; high requirements for quality of products and terms of delivery of products to customers; the emergence of individual requirements for products, which necessitated the transition to almost individual production with the whole complex of complex organizational and technical measures and system of reorganizations; increased competition. It is substantiated that the implementation of the stated proposals for the activation of innovative activity in construction can serve as a certain impetus for accelerating the scientific and technological development of the domestic economy, the development not only of the construction market, but also the enhancement of Ukraine's competitiveness in the world market, which is especially relevant in modern conditions